ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PRODUKSI DAN PENDAPATAN PENGUSAHA INDUSTRI GENTENG - Putra, I Made Bayu Wira Satya Susila; Yasa, I Nyoman Mahaendra (Buletin Studi Ekonomi, 2019)
Abstract: Analysis of the Influential Factors on the Production and Income of Roof Tile Entrepreneurs. The purpose of this study is to determine the effect of labor and capital on income through production. The analysis technique used in this study is path analysis. The results showed that labor and capital directly had a positive and significant effect on production, and also labor, capital and production directly had a positive and significant effect on the income of tile industry entrepreneurs. The sobel test results show that labor and capital indirectly affect income through production. It is hoped that entrepreneurs can improve the quality of the workforce with the latest production methods by using the latest technology and can add workforce in the field of marketing and financial management, and also increase capital for optimal raw material purchases and to increase competitiveness. Entrepreneurs can increase production by marketing it through digital media such as social media and e-commerce that can increase revenue optimally.